Spring 1994 Iowa field report, Chris Edwards - Edwards, Chriset al (1994)
An annotated list of birds sighted by Chris Edwards and four others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1994. Plustek - flatbed